2017
DOI: 10.1038/s41598-017-04824-0
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of ON1 genotype of human respiratory syncytial virus subgroup A in China between 2011 and 2015

Abstract: A molecular epidemiological study of human respiratory syncytial virus (HRSV) was conducted to examine the distribution of its subgroups and genotypes, as well as to identify its transmission pattern in China. A total of 705 samples collected from 9 provinces in China between January 2008 and February 2015 were identified as HRSV-positive and were subsequently sequenced. Of these, 336 samples were HRSV subgroup A (HRSVA), 368 samples were HRSV subgroup B (HRSVB), and 1 sample contained both HRSVA and HRSVB. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 46 publications
6
32
0
Order By: Relevance
“…While most of Chinese viruses , European viruses and Indian surrounding viruses, which solely clustered in genotype C, D, and F, respectively, showing geographic distribution circumscribed characterization. This is similar to other EV, like EV-A71 1 , but different with respiratory viruses such as measles 43 , 44 and human respiratory syncytial viruses 45 , 46 , which spread globally and different genotypes distributed cross over with each other in phylogenetic tree, not much geographic distribution circumscribed characterization.…”
Section: Discussionsupporting
confidence: 64%
“…While most of Chinese viruses , European viruses and Indian surrounding viruses, which solely clustered in genotype C, D, and F, respectively, showing geographic distribution circumscribed characterization. This is similar to other EV, like EV-A71 1 , but different with respiratory viruses such as measles 43 , 44 and human respiratory syncytial viruses 45 , 46 , which spread globally and different genotypes distributed cross over with each other in phylogenetic tree, not much geographic distribution circumscribed characterization.…”
Section: Discussionsupporting
confidence: 64%
“…In a previous study, we found that HRSVB predominated between 2008 and 2010 in China while HRSVA predominated in 2010 and 2012, and both subgroups co-circulated in China till March 2014 18 . We also reported that the ON1 genotype became the predominant genotype of HRSVA circulating in China between 2013 and 2015.…”
Section: Introductionmentioning
confidence: 76%
“…Of these, 295 samples were identified as HRSVA and 360 were identified as HRSVB, and 1 sample was identified to be positive for both HRSVA and HRSVB. Analysis of the HRSVA sequences has been reported previously 18 . In this study, 361 HRSVB sequences, together with sequences from 2 HRSVB samples collected from Jilin in 1991, as well as sequences from 2 HRSVB samples collected from Beijing in 2004, were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014-2015 was also the highest epidemic year for RSV-A, it was deduced that before 2012, the prevalent RSV genotype was NA1 from Chongqing, but in 2014, due to staff turnover, a new Hong Kong strain of ON1 genotype was introduced (Song et al, 2017), evolved, and became the dominant strain. Furthermore, because the population lacked antibody protection, the new genotype spread rapidly and caused the high incidence of RSV-A in 2014-2015 in Guangzhou.…”
Section: Discussionmentioning
confidence: 99%